Dependence of image quality on the length of the reconstructing wave - Sagynbaev, A.A.; Ismanov, Y.H. (Recent Contributions to Physics, 2015)
The article describes the method of the rainbow hologram recording without using real or synthesized slit. If the hologram is illuminated by white light, then the image of the object painted in bright colors is restored. It is also shown that the reconstructed rainbow image can be considered as the sum of the images reconstructed by different wavelengths. In general, these wavelengths are different from the length of the recording wave. This fact results in a slight distortion of the rainbow image. It is shown that the reconstruction of the hologram by the light whose wavelength is different from the length of the recording wave leads to a change in the two most important characteristics of the image that affect the quality of these images: the angular size and zoom images. Results of wavelength influence on the quality of the reconstructed image are represented. Investigations were carried out with the help of computer simulations of the recording and reconstruction of rainbow holograms based on slitless method. The research results can be used to develop a complete computer model to synthesize rainbow holograms recorded by the slitless method.